Grieving as a practice of resistance: Bishnoi entanglements with the Indian nuclear state - Huria, Sonali (Taylor and Francis, 2023)
Bishnoi identity and world-making, engendered through everyday practices of ecological conservation and religious worship, have made this Vaishnavite sect exemplary grassroots environmentalists in the Indian sub-continent. Bishnoi settlements, as sites of abundant green cover and wildlife, are protected and deeply revered by the community. However, their placid lives and shared spaces across villages in Gorakhpur in the state of Haryana, India, transformed into sites of exceptional protests in the last decade. The totalising impulses of the Indian nuclear state threatened to decouple the efficacious intimacies of the bodily-material and human-(non)human through the acquisition of traditional Bishnoi lands and the fencing off of their sacred groves and pastures. When their material world and its inhabitants were threatened by the imposition of a nuclear power plant in their vicinity, the Bishnoi also became political and legal activists. Based on extensive interactions with the Bishnoi community in Gorakhpur and discursive explorations of the legal texts pertaining to the proceedings of the case filed by the community in court, this chapter explores contestations between the Indian state, besotted with the nuclear age, and the intimacies of ecological subjects, deeply committed to protecting their sacred material worlds, and how these discordant enchantments are articulated.
CRIS-Team Scopus Importer:2023-11-03